ANALISIS KESALAHAN MOROFOLOGI SOAL BAHASA ARAB DAN IMPLIKASINYA TERHADAP PEMBELAJARAN - Ai Suaidah; Septi Nurullaily; Silmy Hasya Behesyti (JURNAL EDUCATION AND DEVELOPMENT, 2024)
Analysis of Arabic morphological errors is an effort to examine errors that occur in the order of words in Arabic. The aim of this research is to find out the errors contained in class VIII Arabic questions. The method used in this research is qualitative research. The technique used in data collection is literature study. The results of the research showed that writing errors occurred in the selection of mudzakkar and mu'annats forms as many as 4 errors, writing fi'il either fi;il madhi or mudhari' in terms of tashriif al-lughawy as many as 4 errors, errors in writing hamzah which should have been hamzah washal became hamzah qatha' as many as 5 mistakes.